2022
DOI: 10.1128/aem.01177-22
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing-Based Characterization of Listeria Isolates from Produce Packinghouses and Fresh-Cut Facilities Suggests Both Persistence and Reintroduction of Fully Virulent L. monocytogenes

Abstract: Listeria monocytogenes is of particular concern to the produce industry due to its frequent presence in natural environments as well as its ability to survive in packinghouses and fresh-cut processing facilities over time. The use of whole-genome sequencing, which provides high discriminatory power for the characterization of Listeria isolates, along with detailed source data (isolation date and sample location) shows that the presence of Listeria in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…The present study provides insights into the pathogenic potential and persistence of the L. monocytogenes isolates recovered from a cheese processing facility. The findings of this work should be useful as they could be utilized for epidemiological investigations of L. monocytogenes in the food processing environment, revealing possible contamination scenarios, acquired antimicrobial resistance along the food production chain and providing critical information for post-outbreak management in the facility [ 103 , 104 , 105 ]. These findings also suggest that further research is needed for definitive genome mapping of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides insights into the pathogenic potential and persistence of the L. monocytogenes isolates recovered from a cheese processing facility. The findings of this work should be useful as they could be utilized for epidemiological investigations of L. monocytogenes in the food processing environment, revealing possible contamination scenarios, acquired antimicrobial resistance along the food production chain and providing critical information for post-outbreak management in the facility [ 103 , 104 , 105 ]. These findings also suggest that further research is needed for definitive genome mapping of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the 303 putatively persistent Listeria isolates characterized through WGS were assigned into initial hqSNP clusters based on a relatively high initial hqSNP distance cut-off (i.e., ≤50 pairwise hqSNP differences between one or more isolates within a given hqSNP cluster). While some studies have reported using a similar strategy (Pettengill et al, 2022; Sullivan et al, 2022; Wang et al, 2018), others with a similar number of isolates have reported using lower SNP distance cut-offs, such as ≤20 or ≤10 SNPs, to assign clusters for further analysis (Andrews et al, 2023; Castro et al, 2021; Lucchini et al, 2023), as they may be more likely to indicate that two or more isolates originated from the same source, e.g., the same plant (Pightling et al, 2018). Importantly, in this study we identified key trends among hqSNP clusters that contained isolates with >21 hqSNP differences that might not have been captured if a lower initial SNP distance cut-off was employed.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates <100 kSNPs apart identified based on kSNP3 analysis were then analyzed using the Center for Food Safety and Applied Nutrition (CFSAN) SNP pipeline v. 2.2.1 to identify any preserved hqSNPs existing between groups of isolates (Davis et al, 2015). The reference assembly for the CFSAN SNP pipeline was selected as previously described (Sullivan et al, 2022). After hqSNP analysis was performed for groups of isolates with <100 kSNP differences, isolates that showed >50 pairwise hqSNP differences from all other isolates in the group were removed, and the group was re-examined to obtain “hqSNP clusters” which only included isolates that showed ≤50 pairwise hqSNP differences from at least one other isolate in the cluster.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial positive food samples from the monitoring were not enough to pinpoint the exact source of contamination in five of the nine clusters, emphasizing that the point in the production chain at which the food product tests positive does not have to be the origin of the contamination. Nevertheless, this information can still indicate that hygienic measures have to be taken or that shelf-life studies should be reviewed at different levels of the production chain due to previously underestimated levels of cross-or post-contamination [24].…”
Section: Discussionmentioning
confidence: 99%